Implementation of Good Corporate Governance, Risk Management, and Financial Digitalization on Bank Performance and Their Impact on Firm Value - Aminudin Aminudin; Hari Gursida; Yohanes Indrayono (Return : Study of Management, Economic and Bussines, 2025)
This study aims to analyze the influence of Good Corporate Governance (GCG), risk management, and financial digitalization on bank performance and their impact on company value. This research fills a literature gap by simultaneously analyzing the relationship among these three strategic factors and their combined effect on banking performance and company value, specifically within the context of the Indonesian banking industry confronting OJK regulatory dynamics, digital competition, and global market pressures. The study employs a quantitative approach using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The data are sourced from the annual and sustainability reports of KBMI 3 and KBMI 4 banks over specific periods, utilizing financial performance indicators and company value measures. The study’s results show that (1) GCG does not affect bank performance but has a positive effect on company value; (2) risk management negatively affects bank performance but does not influence company value; (3) financial digitalization positively affects bank performance but does not influence company value; (4) bank performance itself does not affect company value; and (5) mediation testing indicates that bank performance does not mediate the influence of GCG, risk management, or financial digitalization on company value, although the direction of relationships shows varying positive and negative effects. These findings, aligned with previous literature, demonstrate that the influence of GCG, risk management, and digitalization on corporate performance and value is contextual, shaped by the specific indicators applied and the mechanisms examined.